PENGARUH MOTIVASI KERJA, KEPUASAN KERJA DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI PT MDH DI JAKARTA - Nimas Kartika Dewi; Yohanes Temaluru (Media Bina Ilmiah, 2024)
Abstract The research aims to evaluate the influence of work motivation, job satisfaction, and organizational culture on PT's organizational commitment. MDH. The research method used is quantitative with Structural Equation Modeling (SEM) analysis using the Partial Least Square (PLS) approach. The research population includes all staff level employees up to senior managers at PT. MDH as many as 70 people, with a total sampling technique. The research results show that work motivation has a positive influence on organizational commitment, job satisfaction also has a positive influence on organizational commitment. Organizational culture does not have a positive effect on organizational commitment, work motivation, job satisfaction, and organizational culture has a positive and significant effect on organizational commitment in PT MDH employees simultaneously